Photoperiod sensing of the circadian clock is controlled by EARLY FLOWERING 3 and GIGANTEA. (11th December 2019) - Anwer, Muhammad Usman; Davis, Amanda; Davis, Seth Jon; Quint, Marcel
Summary: ELF3 and GI are two important components of the Arabidopsis circadian clock. They are not only essential for the oscillator function but are also pivotal in mediating light inputs to the oscillator. Lack of either results in a defective oscillator causing severely compromised output pathways, such as photoperiodic flowering and hypocotyl elongation. Although single loss of function mutants of ELF3 and GI have been well studied, their genetic interaction remains unclear. We generated an elf3 gi double mutant to study their genetic relationship in clock‐controlled growth and phase transition phenotypes. We found that ELF3 and GI repress growth differentially during the night and the day, respectively. Circadian clock assays revealed that ELF3 and GI are essential that enable the oscillator to synchronize the endogenous cellular mechanisms to external environmental signals. In their absence, the circadian oscillator fails to synchronize to the light–dark cycles even under diurnal conditions. Consequently, clock‐mediated photoperiod‐responsive growth and development are completely lost in plants lacking both genes, suggesting that ELF3 and GI together convey photoperiod sensing to the central oscillator. Since ELF3 and GI are conserved across flowering plants and represent important breeding and domestication targets, our data highlight the possibility of developing photoperiod‐insensitive crops by adjusting the allelic combination of these two key genes. Significance Statement: Anticipation and timely response to day‐length variation are key to plant fitness and survival. Circadian clocks are fundamental internal time‐keeping mechanisms enabling plants to anticipate and respond to day‐length changes. To achieve this, plants constantly integrate external light signals and internal cellular mechanisms and ensure that both external and internal processes are well synchronized. Here, we report that ELF3 and GI are essential for photoperiod sensing.